Początki kultu maryjnego na ziemiach polskich - Kochaniewicz, Bogusław (Poznańskie Studia Teologiczne, 2018)
This article is an attempt to reconstruct the devotion to the Blessed Virgin Mary at the beginning of the Polish state. Based on the liturgical books and the calendars from the 9th–11th centuries preserved in Polish archives, the form of the Marian devotion in the Poznań diocese was sought. Despite the lack of preserved monuments representing the oldest Polish diocese, it was established that the service to the Blessed Virgin Mary had a liturgical character. The four main feasts in hon- or of the Mother of God, celebrated in the Western Church, were celebrated in Poznań, too. An analysis of the oldest liturgical formularies preserved in Polish and Western archives did not yield satisfactory results. Based on the available monuments, it is not possible to determine the content of the formularies destined for Marian feasts celebrated in Poznań.